Stress and Depression among undergraduate Medical Students of Bangladesh (Bangladesh Journal of Medical Education, 2014)
This cross-sectional descriptive type of study was conducted to explore the level of stress and depression and to find out the various socio-demographic, academic factors which act as barriers to study among undergraduate medical students of Bangladesh. The study was conducted at Dhaka Medical College during the period of April 2009 to June 2009. The students of 1st year to 5th year were the study population. A total of 425 students participated in the study. After taking proper approval from the concerned authority adopting convenient sampling technique data were collected through a self administered questionnaire with validated Kessler 10 psychological distress scale. The study revealed that only (1%) respondents were free from any sorts of psychological stress. Over one third (34.6%) had mild stress, (39.8%) moderate stress and about one fourth (24.9%) was suffering from severe stress according to Kessler 10 Psychological distress scale. A significant proportion of male respondents (73%) had moderate to severe psychological distress compared to the female respondents (56%) p